2018
DOI: 10.1080/00952990.2018.1491587
|View full text |Cite
|
Sign up to set email alerts
|

Substance-use disorders, personality traits, and sex differences in institutionalized adolescents

Abstract: This study provides a relative evidence for sex specificities in the relation between PD traits and SUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…One limitation of the study is that was not possible to diagnose personality orders with the diagnostic system DIA-X. However, antisocial, borderline, and paranoid personality disorders were associated strongly with substance-use disorders ( 58 60 ). Therefore, determining the prevalence of personality disorders would provide interesting insights into the mental health of this particular study population, which has an extremely high rate of substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the study is that was not possible to diagnose personality orders with the diagnostic system DIA-X. However, antisocial, borderline, and paranoid personality disorders were associated strongly with substance-use disorders ( 58 60 ). Therefore, determining the prevalence of personality disorders would provide interesting insights into the mental health of this particular study population, which has an extremely high rate of substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Atrelada à escola, o contexto familiar é de suma importância no desenvolvimento de crianças e adolescentes, pois as relações estabelecidas nesse ambiente são decisivas em comportamentos anti ou pró-sociais 2,16 . As relações familiares aqui analisadas, mostraram que 27% dos adolescentes faziam parte de famílias nucleares compostas por pai e mãe, 21% pertencia a famílias reconstituídas (padrasto e madrasta), portanto, evidencia que a maioria mora com ambos os pais ou pelo menos com um dos pais.…”
Section: Discussionunclassified
“…A institucionalização, vista a partir de um caráter de problema social e de saúde que afeta a maior parte dos territórios, é desencadeada a partir da ocorrência do ato infracional e da construção do sujeito individual e social dentro de um cenário de vulnerabilidade e violência. Os transtornos de personalidade associados ao uso de substâncias psicoativas são considerados fatores agravantes ao desenvolvimento do ato infracional 2 .…”
Section: Introductionunclassified
“…Herbasaat (2018) linked the characteristics of these PD to SUD to reduce internal tension. 21 Based on sex distribution, the prevalence of SUD between men and women with a BPD is similar. However, in the treatment sample, men were over-represented which indicated men had more severe substance use difficulties than women as shown in Table 1.…”
Section: Between Personality Disorder and Substance Use Disordermentioning
confidence: 99%
“…Bernstein, Stein and Handelsman (in Herbasaat, 2018) found that antisocial behaviour was very common among drug users and other substance abusers, where 25-50% of those diagnosed with SUD also met the criteria for antisocial personality disorder. 21 Antisocial PD (APD) tend to have more severe alcohol use disorders with earlier onset of consumption and more rapid development of dependent symptoms. 17 APD traits such as deficits in executive function and response regulation, and anxietyimpulsive personality traits also have a greater tendency to develop cocaine and amphetamine use disorders.…”
Section: Between Personality Disorder and Substance Use Disordermentioning
confidence: 99%